1996
DOI: 10.1007/bf02782758
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glutamate receptor subtype mRNAs in gonadotropin-releasing hormone neurons in rat brain

Abstract: The aims of the present study were to determine: 1. If glutamate neurites can provide input to gonadotropin-releasing hormone (GnRH) neurons; 2. Which glutamate receptor subtype mRNAs are expressed in GnRH neurons; and 3. If GnRH neurons synthesize kainate 2 receptor (KA(2)) protein. Immunohistochemical double stainings for GnRH and glutamate or for GnRH and KA(2)-receptor protein were applied to rat brain sections containing the medial septum-diagonal band and preoptic area or the median eminence; in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 31 publications
1
33
0
2
Order By: Relevance
“…The MBH has been well demonstrated to contain EAA receptors according to studies using immunocytochemistry [14,15], in situ hybridization [15,22], and binding assay [23,24]. Moreover, glutamate stimulates in vitro LHRH release from the ARC-ME fragments [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MBH has been well demonstrated to contain EAA receptors according to studies using immunocytochemistry [14,15], in situ hybridization [15,22], and binding assay [23,24]. Moreover, glutamate stimulates in vitro LHRH release from the ARC-ME fragments [16].…”
Section: Discussionmentioning
confidence: 99%
“…ity of LHRH neurons terminate. This is because the MBH has been demonstrated to be one of the major action sites of EAAs to stimulate LHRH release according to immunohistochemical studies [14,15] or an in vitro study showing the stimulatory effect of EAA on LHRH release from the arcuate nucleus-median eminence (ARC-ME) fragments [16]. Although a previous study reported that EAA release in the MBH does not increase during LH surges induced by E 2 treatment alone in OVX rats [17], it remains to be determined if EAAs increase during progesterone-enhanced LH surges in E 2 -treated OVX rats.…”
mentioning
confidence: 99%
“…223). Only small subpopulations of GnRH neurons in the rat have been reported to express NMDA and/or kainate receptors (228,229), and terminals containing glutamate have been demonstrated to synapse on GnRH neurons in the monkey (230). Neurons throughout the preoptic area and hypothalamus, including the AVPv, have been shown to express all three types of ionotropic excitatory amino acid receptors (223,231,232).…”
Section: June 1998 Estrogen Inputs To Gnrh Neurons 311mentioning
confidence: 99%
“…to a lesser extent, by kainate receptors. However, it has been shown previously that less than 5% of GnRH neurons contain NMDAR1 mRNA [ 16,25,26] which encodes the common required subunit for a func tioning NMDA heteromeric glutamate receptor [27], al though recently the presence of NMDAR 1 immunoreactivity in certain GnRH neurons was reported [28]. In stead.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that GnRH neurons ex press several different glutamate receptor subunit mRNAs [16]. In the adult female rat, a subset of GnRH neurons expresses the kainate-preferring glutamate recep tor subunit KA2 (32% of GnRH neurons) or the NMDApreferring subunit NMDAR2A ( 17% of GnRH neurons).…”
Section: Introductionmentioning
confidence: 99%